PENGALAMAN PERAWAT SEBAGAI SURVIVOR DAN PEMBERI PERTOLONGAN KESEHATAN SAAT RESPON TANGGAP DARURAT PADA KORBAN BENCANA TSUNAMI TAHUN 2004 DI LHOKNGA DAN LHOONG ACEH BESAR - Sapondra Wijaya; Sri Andarini; Setyoadi - (Fakultas Ilmu Kesehatan, 2015)
Background: Fast response in emergency response phase of a disaster is very important. Fast response will be hard to do if a disaster such as the tsunami in 2004 happen, which makes an isolated area. The inhibition are destruction of communication and transportation networks, lack of logistics and the most fatal is the lack of health workers, especially nurses as the greatest number. Nurses in the disaster area at the time it is not only need a knowledge and skills as a first responder but also the mental readiness. Nurses who are save from the disaster or survivor and decided to become a first responder must have good mental strength.Objective: To explore the experience of nurses as survivors and as a health giver during emergency response to victims of the Tsunami 2004 in Lhoknga and Lhoong, Aceh Besar.Methods: Qualitative research with phenomenological intepretif approach. Data were collected through interviews to 5 nurses who met the criteria. Data were analyzed using Braun and Clark thematic analysis.Results: This study resulted 7 themes, namely the psychological reactions of nurses in acute phase of the emergency response, the heroism of a nurse in acute phase, survive in a critical condition, the sense of responsibility of nurses, the emotional bond of nurses and regions, the psychological reactions of nurses after emergency response phase, and nurses willingness of increasing knowledge and skills in disaster management.Conclusion: Providing medical aid at the time it was a response from the appear of heroism a nurse. Another reason nurses become first responder is a form of coping in overcoming grief, the next is a form of their responsibilities as nurses and nurse emotional bond with the disaster area. 11 years after the 2004 tsunami disaster, the knowledge and skills of nurses to respond to disasters did not increase significantly. Keywords: nurse experience, a disaster, first responders, emergency response